Completed fertility effects of family policy measures: Evidence from a life-cycle model - Raphael Abiry; Karsten Reuss; Holger Stichnoth (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We estimate a structural life-cycle model of fertility and female labour supply and use it to evaluate the effects of a number of key family policy measures based on data for Germany. Parental leave benefits, child benefits and subsidized childcare are found to have substantial fertility effects. Without these measures, completed fertility is estimated to be lower by 6%, 7%, and 10%, respectively. Income tax splitting, which is fiscally expensive, reduces female labour supply but has a negligible effect on fertility.
urn:nbn:de:bsz:180-madoc-371419
Keywords: C25; C53; J13; J22; 330; Fertility; female labour supply; family policy; dynamic programming